Teaching style preferred by vocational teachers in relation to their work commitment / Sekeran Apoi - Apoi, Sekeran (2012)
This study was conducted to determine that Teaching Style Preferred By Vocational Teachers in Relation to their Work Commitment in the process of teaching and learning in the classroom. This study used a descriptive survey design targeting all 104 teachers from Secondary School Vocational Matang and Kuching in Kuching, Sarawak. Data was collected using a questionnaire. Descriptive and inferential statistics were used to analyze the data obtained, including frequency counts, means, percentages and ANOVA. The findings shows that "Sharing my knowledge and expertise with students is very important to me" (Mean = 4.664) as the most preferred by vocational teachers; in regard to commitment to teaching "I always enjoy teaching" (M= 4.56) and "I always try to do the best for the weak students" (M= 4.558). In regard to gender, there are significant differences between female teachers (Mean = 4.688) with male teachers (Mean = 4,653) in terms of "Sharing my knowledge and expertise with students is very important to me" (t = 100.162 p <0.001). There are significant correlation between teaching styles and students' enrolments "What I say and do models appropriate ways for students to think about issues in the content" (F = 6.95, p < 05) were the highest. The finding also reveal that the significant correlation between teaching style and commitment to teaching work "I give students a lot of personal support and encouragement to do well in this course" with "I always enjoy teaching" (r = .499; p <01), and "I always try to do the best for the weak students" (r = .455; p < 01) were the highest. "I don 9t make full use of the time in the class allocated for teaching and learning process" (r = - .436; p < 01) showed a significant negative correlation between teaching styles and commitment to teaching work. As a conclusion, the teaching styles preferred by vocational teachers in relation to their work commitments are more female teachers preferred to more female teachers dominantly play the role of Cluster 3 (facilitator or personal model or expert cluster) in their teaching styles as compared with the male teachers. The findings of this study would be usefiil to the interested parties in the field of teaching and learning process that is influenced by thework of teachers in school especially school leaders.